Multiple PCR assay based on the cigR gene for detection of Salmonella spp. and Salmonella Pullorum/Gallinarum identification - Zhou, Ying-ying (Poult Sci, 2020)
Salmonella spp. are important zoonotic pathogens that are responsible for severe diseases in both animals and humans. Salmonella enterica subsp. enterica serovar Gallinarum biovar Gallinarum (S. Gallinarum) and biovar Pullorum (S. Pullorum) are typical infectious pathogens detected in the chicken industry that have caused great economic losses. To facilitate their detection and prevent contamination, we developed a rapid multiple PCR method, which can simultaneously detect Salmonella spp. and further identify the biovars S. Pullorum/Gallinarum. This PCR detection method is based on the cigR gene, which is conserved among Salmonella spp. but has a 42-bp deletion in S. Pullorum/Gallinarum. The specificity and sensitivity of the PCR assay was evaluated with 41 different strains: 34 Salmonella strains, including 5 S. Pullorum/Gallinarum strains, and 7 non-Salmonella strains. The lower limit of detection was 8.15 pg of S. Pullorum (S06004) genomic DNA and 20 cfu in PCR, which shows a great sensitivity. In addition, this method was applied to detect or identify Salmonella from processing chicken liver and egg samples, and the results corresponded to those obtained from serotype analysis using the conventional slide agglutination test. Overall, the new cigR-based PCR assay is efficient and practical for Salmonella detection and S. Pullorum/Gallinarum identification and will greatly reduce the workload of epidemiologic investigation.